PENGABDIAN KEPADA MASYARAKAT DALAM MEMBENTUK KARAKTER PESERTA DIDIK PADA ERA BERMAIN GADGET (HANDPHONE) DI SMP NEGERI 1 AEK KOTA BATU - Irmayanti, Badrul Ainy Dalimunthe, Tetty Rahmiati Harahap, Erni Wahyuni, Rohani (PT.JNDI, JURNAL BIMA, 2024)
This service aims to shape the character and responsibility of students in using and playing with gadgets (cellphones) that are not good. The method used in this activity is through counseling and outreach to students. The results of this activity are expected to be that students can use their cellphones or gadgets for learning purposes at school, not just for fun and playing games. Because at SMP Negeri 1 Aek, Batu City, many students already have cellphones, which means these cellphones will have a big influence on minors. This cellphone could be a threat to students who are important as the nation's next generation because technological developments in children can create very bad character. Children become addicted to playing on cellphones without time limits. Even though underage children still need education, which is very important for survival. A child's good and bad character can change over time, especially bad character will emerge due to the negative influence of technological developments that are misused by certain individuals. Even parents of a child easily give their child a cell phone to make their child quiet even though this can have an impact. hurry for the child.